2022
DOI: 10.1126/scitranslmed.abq0095
|View full text |Cite
|
Sign up to set email alerts
|

A tetravalent TREM2 agonistic antibody reduced amyloid pathology in a mouse model of Alzheimer’s disease

Abstract: Triggering receptor expressed on myeloid cells 2 (TREM2) plays crucial roles in Alzheimer’s disease (AD) by regulating microglia migration toward, and phagocytosis of oligomeric amyloid-β (oAβ) and amyloid plaques. Studies in rodent models of AD have shown that mice with increased TREM2 expression have reduced amyloid pathology. Here, we identified a TREM2 agonist monoclonal Ab (Ab18) by panning a phage-displayed single-chain variable fragment Ab library. By engineering the bivalent immunoglobulin G1 (IgG1) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…The association between Alzheimer’s β-amyloid deposition and sTREM2 [ 316 ] points to the notion that one can leverage treatments of microglia-modulating and anti-amyloid therapeutics by targeting, e.g., TREM2 or CD33 . Recent studies showed the promising effects of increasing TREM2 in a mouse model using an agonistic antibody design [ 317 ]. However, the temporal component is crucial and a beneficial effect of increasing TREM2 is observed, especially in the early stage of AD development, highlighting the dynamic role of TREM2 in modulating β-amyloid deposition and neuritic dystrophy in AD pathogenesis [ 317 , 318 ].…”
Section: Ad Therapeutics: Challenges and Opportunitiesmentioning
confidence: 99%
“…The association between Alzheimer’s β-amyloid deposition and sTREM2 [ 316 ] points to the notion that one can leverage treatments of microglia-modulating and anti-amyloid therapeutics by targeting, e.g., TREM2 or CD33 . Recent studies showed the promising effects of increasing TREM2 in a mouse model using an agonistic antibody design [ 317 ]. However, the temporal component is crucial and a beneficial effect of increasing TREM2 is observed, especially in the early stage of AD development, highlighting the dynamic role of TREM2 in modulating β-amyloid deposition and neuritic dystrophy in AD pathogenesis [ 317 , 318 ].…”
Section: Ad Therapeutics: Challenges and Opportunitiesmentioning
confidence: 99%
“…Therefore, engineered antibodies hold great promise to treat AD. A bispecific antibody consisting of a tetravalent TREM2-targeting antibody and an antibody targeting the mouse transferrin receptor (TREM2/αTfR bispecific Ab) has been developed, which strongly facilitates brain delivery and increases microglial TREM2 activation [210]. It is noteworthy that contrasting effects of TREM2 activation have been reported in different AD pathologies and disease stages, suggesting TREM2 activation may be beneficial in a certain time window and in Aβ pathology rather than tau pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that CELF1 is involved in the regulation of alternative splicing for exon 3 of the TREM2 locus (Yanaizu et al, 2020), which serves to make a triggering receptor protein that plays crucial roles in AD pathophysiology. TREM2 regulates microglial migration toward and phagocytosis of amyloid-beta plaques and studies in rodent models have shown that increased TREM2 expression has reduced amyloid pathology (Zhao et al, 2022). This evidence is further supported given that CELF1 expression is enriched within microglia.…”
Section: Discussionmentioning
confidence: 99%